Resource scarcity - A global security threat? - Stormy Mildner; Solveig Richter; Gitta Lauster (Stiftung Wissenschaft und Politik (SWP), 2011)
For a decade we have been living through a period of great turbulence in the commodity markets. Rising and sometimes highly volatile prices, strong geological and market concentration, and state intervention in the commodity markets all stoke fears of future supply bottlenecks and an expectation of ensuing international tension and violent confrontation. The list of recent incidents is long: the gas dispute between Russia, Ukraine and the EU; food revolts in Haiti, Tunisia and Algeria; China's trade conflict with the United States and the EU over export restrictions imposed on many metals; and the confrontation between China and Japan over China's export ban on rare earths to name just a few. Without doubt, increasing competition for natural resources poses considerable conflict potential. It can further destabilise already fragile countries and regions or inject tension into otherwise cooperative inter-state relations, so conflict risks are found at different levels: within the producing and consuming countries and in relations between them. But the phenomenon of competition leading directly to conflict is not observed in every case. Sometimes new patterns of cooperation emerge. The central questions of the study 'Resource Scarcity - A Global Security Threat?' are therefore: Under what circumstances does resource scarcity lead to conflicts? And how can latent and acute conflicts over scarce resources be contained and regulated?
Keywords: 320; Global